We the Kids : The Preamble to the Constitution of the United States - Catrow, David (New York : Dial Books for Young Readers, 2002)
An illustrated preamble to the Constitution of the United States.
Keywords: Constitutional law -- Juvenile literature. -- United States; Constitutional law -- United States